Special investigative methods and the authenticity of evidence derived from them in corruption crimes - Researcher: Maeda Hussein Majeed; Dr. Mohammed Hameed Abed (The college of law and political science journal, 2023)
In the face of the prevalence of corruption offences and their complexity and organization, the methods of investigation and collection of traditional evidence are no longer sufficient and effective to counter them. This necessitated the need to adopt modern procedures in line with their criminal methods. and, accordingly, the United Nations Convention against Corruption includes an exception to the use of special investigative techniques to detect corruption offences because the public interest is weighed against the personal interest, However, the expansion of these procedures may compromise human rights and fundamental freedoms. In order to accept evidence derived from special investigative techniques for convictions for corruption offences, it must be based on national legislation that establishes the controls and conditions of recourse and regulates their effects and nullity, thereby nullifying proceedings and wasting evidence.